The Traditionalism of Rene Guenon in the Discourse of Philosophy of History and Social Anthropology - Karimov, Rakhmat; Bekbaev, Rauf (Տիգրան Մեծ)
The article provides a complex analysis of the problems of traditionalism in the teaching of Rene Guenon, a famous French philosopher author of works on metaphysics, symbolism and initiation. Attention is drawnto the fact that traditionalism sublimated and produced a theoretical formulation of ideals, systems, values aimed at the conscious cultivation of this worldview. The roots of the philosophical reflection of traditionalism, which originatedin ancient times, starting with ancient Chinese and ancient Indian philosophy, through ancient Greek philosophy to its modern doctrines, are analyzed. The concept of Tradition, which Guenon defined as the so-called Primordial Tradition, is considered. A comparative analysis of the problem of intellectual intuition of Rene Guenon and Henri Bergson in the context of social philosophy is carried out. Particular attention is paid to the concept of Rene Guenon‟s philosophy of history, in which the basic position is occupied by the theory of cosmic cycles based on the cosmology of Hinduism.
Keywords: Philosophy